2011
DOI: 10.1603/ec10151
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by Flea Beetles (Coleoptera: Chrysomelidae; Phyllotreta spp.) Is Decreased on Canola (Brassica napus) Seedlings With Increased Trichome Density

Abstract: Laboratory and Þeld studies were undertaken to determine the effects of increased numbers of trichomes on seedling stems, petioles, and Þrst true leaves of Brassica napus L., canola, on the feeding and behavior of the crucifer ßea beetle Phyllotreta cruciferae (Goeze) (Coleoptera: Chrysomelidae). Seedlings of ÔWestarÕ canola with genes inserted from Arabidopsis thaliana L. for increased trichome production, called Hairy1, were tested against Westar seedlings in no-choice and choice laboratory tests, and agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 47 publications
2
34
0
3
Order By: Relevance
“…In Brassicaceae plants, evidence is accumulating to suggest that genetic variation within a plant species alters insect community composition and, in turn, exerts selection on plant defense [4, 79, 80]. Variation in the trichome density is also observed across Brassicaceae plants [71, 72, 73], where GL1 orthologs affect the trichome density [81]. In the context of community genetics, the present study on GL1 provides evidence of a key gene affecting the community composition of crucifer-feeding insects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brassicaceae plants, evidence is accumulating to suggest that genetic variation within a plant species alters insect community composition and, in turn, exerts selection on plant defense [4, 79, 80]. Variation in the trichome density is also observed across Brassicaceae plants [71, 72, 73], where GL1 orthologs affect the trichome density [81]. In the context of community genetics, the present study on GL1 provides evidence of a key gene affecting the community composition of crucifer-feeding insects.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have reported associations between GL1 polymorphism and anti-herbivore functions in field populations of A. lyrata [9, 10] and A. halleri [11, 18]. Plant trichomes also prevent herbivory by sawflies [71] and flea beetles [72, 73] on Brassica cultivars. Together with these results, our present results indicate that plant trichomes and a single gene GL1 play a key role in physical defense against crucifer feeders.…”
Section: Discussionmentioning
confidence: 99%
“…Glandular trichomes on crop and non‐crop plants can store and secrete exudates containing chemicals that repel, impede movement or even trap insects and mites, resulting in their death from desiccation or starvation . Plant breeding programs have successfully produced plant accessions and cultivars (or varieties) of crop plants that express increased trichome density, resulting in increased resistance to attack from some herbivores . Therefore, trichome‐based plant defense is an important mechanism of pest suppression for the agricultural community …”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by transferring the AtGL3 trichome regulatory gene from Arabidopsis thaliana into the OSR genome, followed by the knock‐down of the BnTTG1 gene to ensure a similar plant growth as the original glabrous cultivar. In laboratory assays as well as in field trials, the resulting “hairy canola” (Gruber et al., ) was clearly more resistant to flea beetles ( Phyllotreta cruciferae and P. striolata ) and to the diamondback moth (Alahakoon, Adamson et al., ; Alahakoon, Taheri et al., ; Soroka, Holowachuk, Gruber, & Grenkow, ).…”
Section: Sources Of Resistance and Introgression Into Osrmentioning
confidence: 99%
“…to the diamondback moth (Alahakoon, Adamson et al, 2016;Alahakoon, Taheri et al, 2016;Soroka, Holowachuk, Gruber, & Grenkow, 2011).…”
Section: Strategy 1: Introduction Of Transgenes Into the Osr Genomementioning
confidence: 99%